2022
DOI: 10.3390/brainsci12060701
|View full text |Cite
|
Sign up to set email alerts
|

Stance Phase Gait Training Post Stroke Using Simultaneous Transcranial Direct Current Stimulation and Motor Learning-Based Virtual Reality-Assisted Therapy: Protocol Development and Initial Testing

Abstract: Gait deficits are often persistent after stroke, and current rehabilitation methods do not restore normal gait for everyone. Targeted methods of focused gait therapy that meet the individual needs of each stroke survivor are needed. Our objective was to develop and test a combination protocol of simultaneous brain stimulation and focused stance phase training for people with chronic stroke (>6 months). We combined Transcranial Direct Current Stimulation (tDCS) with targeted stance phase therapy using Virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…Recently, Salameh et al. investigated the effect of combined VR and tDCS stimulation and found it to be effective in the rehabilitation of gait and lower-limb function [ 114 ]. In the current study, we also found that the combined therapy was effective; however, other studies that used tDCS stimulation of the M1 and cerebellum together [ 50 , 65 ] did not use a similar intervention combination.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Salameh et al. investigated the effect of combined VR and tDCS stimulation and found it to be effective in the rehabilitation of gait and lower-limb function [ 114 ]. In the current study, we also found that the combined therapy was effective; however, other studies that used tDCS stimulation of the M1 and cerebellum together [ 50 , 65 ] did not use a similar intervention combination.…”
Section: Discussionmentioning
confidence: 99%
“…Others have published preliminary work on adding brain stimulation methods to the treatment of the lower limb after stroke [ 49 , 51 , 52 , 53 , 54 , 55 ], and the results are somewhat promising [ 49 , 51 , 52 , 53 , 54 , 55 ]. In chronic stroke, one recent study demonstrated the feasibility of administering targeted tDCS brain stimulation during stance phase walking training, designed and framed within neuroplastic motor learning principles [ 56 ].…”
Section: Hypotheses and Rationalementioning
confidence: 99%
“…Tran-scranial direct current stimulation (tDCS) is a priming technique that modulates membrane potential and initiates synaptic plasticity in the area of application as well as the adjacent neural networks ( Stagg and Nitsche, 2011 ). TDCS stimulation in addition to therapies including conventional rehabilitation, robotics based rehabilitation, virtual reality, physical therapy and other techniques is a promising intervention to enhance motor performance, balance and gait in stroke patients ( Geroin et al, 2011 ; Seo et al, 2017 ; Picelli et al, 2018 ; Ehsani et al, 2022 ; Salameh et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%